The Analysis of Student Learning Outcome Using a Probing Prompting Learning Model - Tuerah, Philoteus; Eleonora Regar, Vivian; Javier C. Tuerah, Ignatius (International Journal of Psychosocial Rehabilitation, 2020)
This research is experimental research with a two-factor factorial design, conducted at Eben Haezar High School in Manado. The research subjects were Class XI MIA students consisting of two classes, where 33 students in Class XI B received prompting probing treatment and 34 students in Class XI C received direct learning treatment. The purpose of this study was to describe the effectiveness of the prompting probing learning model and analyze the interactions between the prompting and direct learning probing models with numerical abilities on the mathematics learning outcomes. From all students who took part in learning activities with this model, the results were observed when presenting the results of their respective groups. Of the 31 who attended the study, there were 27 students, or 83.87%, able to answer questions well; 23 students, or 74.19%, could give reasons for the answers given; and there are 20 students, or 64.5%, who have dared to give a response. Likewise, for learning completeness, classical learning completeness has met the minimum completeness requirements of 80%. There is an interaction between the mathematics learning outcomes of conical slices of class XI MIA who are given probing treatment and direct learning in terms of numerical abilities.